1999
DOI: 10.1126/science.286.5448.2319
|View full text |Cite
|
Sign up to set email alerts
|

Deflection of the Local Interstellar Dust Flow by Solar Radiation Pressure

Abstract: Interstellar dust grains intercepted by the dust detectors on the Ulysses and Galileo spacecrafts at heliocentric distances from 2 to 4 astronomical units show a deficit of grains with masses from 1 x 10(-17) to 3 x 10(-16) kilograms relative to grains intercepted outside 4 astronomical units. To divert grains out of the 2- to 4-astronomical unit region, the solar radiation pressure must be 1.4 to 1.8 times the force of solar gravity. These figures are consistent with the optical properties of spherical or elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 25 publications
4
60
0
Order By: Relevance
“…It was found that the dominating flux consists of approximately 0.3 μm particles that had a maximum β-value of >1 because an exclusion zone of small particles reached out to about 3 AU (Landgraf et al 1999a). Measurements by this spacecraft found a long-term variation in the ISD flow by about a factor 3.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…It was found that the dominating flux consists of approximately 0.3 μm particles that had a maximum β-value of >1 because an exclusion zone of small particles reached out to about 3 AU (Landgraf et al 1999a). Measurements by this spacecraft found a long-term variation in the ISD flow by about a factor 3.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, a set of measurements at different positions, times, and/or particle masses will constrain the β and Q/m values for these particles, so it will constrain the physical and compositional properties of interstellar grains. Previously Landgraf et al (1999a) succeeded at such an analysis using the effect of β on the mass distribution. Figure 15 gives an overview of the parameters of the performed simulations.…”
Section: Overview Of Used β and Q/m-valuesmentioning
confidence: 99%
See 2 more Smart Citations
“…1). For this we assumed a β-curve based on the "astronomical silicates" curve from Gustafson (1994) but with β-values adapted to the results of Landgraf et al (1999) who assume densities of 2000 kg m −3 . We call this the β-curve of the reference material or the "reference curve" in this paper.…”
Section: Gravity and Radiation Pressure Onlymentioning
confidence: 99%